Variações altitudinais na diversidade e composição em espécies de vespas e abelhas (Hymenoptera: Aculeata) - Lucas Neves Perillo (2011)
Distribution patterns of insects along elevational gradients have been described for many tropical mountains. According to the hypothesis of elevational gradient, species richness and abundance of species tend to decrease in higher altitudes. Aculeata is considered a monophyletic lineage of Hymenoptera order. They are important pollinators, but there are few studies on their ecology and distribution, especially in upper montane environments. In Serra do Caraça, the vegetation is very heterogeneous and also has a large altitudinal range (850-2072 m), fact which allows studies on altitudinal distribution of species. To verify if the assembly of Aculeata vary in structure along the altitudinal gradient, six altitudes were selected. 180 trap-nests were allocated full time in each altitude from October 2009 to October 2010, and nine Moericke traps (armed by 48 hrs from 15 to 15 days). Malaise traps were also set in three out of six sampling points to complement the survey. When possible, active capture effort was also performed with entomological net. A total of 2927 specimens were sampled, divided into 186 morphospecies, grouped into 14 families of Aculeata. There is greater richness of wasps and bees at lower altitudes. No trap-nests were colonized in the most extreme altitudinal point, probably due to resource constraints in higher altitudes habitats. The Moericke trap was the most effective of all methodologies used. Therefore, data obtained from these traps were used to perform analyses of similarity and composition in species. The comparisons were performed using the records of presence or absence of species (Jaccard index) and abundance of morphospecies of Aculeata (Bray-Curtis index: log x +1). Both richness and species composition varied significantly with altitude. Each altitude seems to have its special assortment of morphospecies, despite of the closest points were more similar. The results also indicate the effect of estacionality on the species composition. Through capture efficiency analysis of different trap types, it was found that no species was collected through all devices. The importance of sampling through different methodologies was evident, since each taxonomic group is more effectively captured by a specific type of trap. The clay and silt soils become increasingly scarce in higher altitudes, difficulting nidification of species that uses clay for making its nests. Different soil types also exert influence on vegetation composition, which interferes in composition and abundance of Aculeata assemblages. The altitudinal variation in species composition emphasizes the importance of preserving these mountain tops, which have a history of devastation caused by mining, particularly by the extraction of iron. The results emphasize the importance of study area and adjacents conservation. Besides, the results complemented the knowledge of Aculeata fauna in this region